Qadim dalam Perspektif Ilmu Falak: Studi Analisis Pemikiran Albert Einstein - M. Anzaikhan (Program Studi Aqidah dan Filsafat Islam, 2021)
The debate about the qadim of nature is one of the theological issues that has never been found in agreement among Muslim Scholars. This understanding is based on the way of their thinking and the scientific frame developed among Muslim scholars. If the concept of qadim is related to the context of time, qadim means a reality that is considered to have existed before time. Based on that argument, the question arised is whether that the time existed before nature or did that time occur due to the movement of the nature? This study uses a qualitative approach, while data obtained from the study of literature and some related documents. The data verification process is carried out by comparing the study of Kalam and Falaq. In the perspective of Kalam, qadim is understood by the scholars rationally (philosophy) while the scholar of Kalam acknowledged it scientifically. This research concludes that Kalam scholars consider time exists due to the movement of the universe, so that nature is considered to have existed before time. Therefore, Kalam scholar regards the nature is qadim.